Effect of anisosmotic stress on the structural and functional integrity of the plasma and acrosomal membrane of ram sperm - Rubio-Guillén, Jorge; Osorio-Meléndez, Carla; González-Villalobos, Decio; Nava-Trujillo, Héctor; Quintero-Moreno, Armando (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The integrity of the plasma membrane (MP) and the acrosome (MA) have been two of the most studied seminal evaluation parameters due to their role as a cell boundary and because they are responsible for interactions between cells effective. To assessing more objectively the effects of osmotic stress on the integrity of the PM and MA, as well as the rate of change that occurred during seminal cryopreservation, five freshly collected ejaculates were evaluated, refrigerated at 5 ºC and thawed per ram/session during 5 consecutive weeks. Using eosin-nigrosin (EN) staining, vitality (VIT), morpho abnormalities and cellular response were evaluated after performing osmotic resistance (ORT) and endosmosis (HOST) tests. The direct effect of anysosmosis and cryopreservation on the dependent variables were analyzed using the GLM procedure (SAS®) and when differences were observed, the effects were quantified using the LSMEANS. All the sperm quality values ​​studied were significantly affected (P <0.001) by cryopreservation (VIT, ORT, HOST). The ORT demonstrated how the acrosome was one of the structures most affected by cryopreservation (P <0.001). In conclusion, the present study confirms that anysosmotic stress affects the sperm cell in an important way, compromising the reference values ​​that quantify semen quality, especially MA and MP.